Optimalisasi Finansial pada Industri Barang Konsumsi: Analisis Faktor-Faktor yang Memengaruhi Cash Holding - Ristianti, Dina Eka; Cahyaningtyas, Fadilla (Universitas Batanghari, 2024)
The purpose of this study is to examine the variables influencing cash holding in consumer products businesses that are listed on the Indonesia Stock Exchange in the 2019–2021 timeframe. Effective financial tactics, particularly cash holding practices, are necessary in a competitive and tightly developed economy. Maintaining cash on hand is critical to the business's ability to remain liquid, particularly in the face of adversity like the Covid-19 outbreak. Growth opportunity, investment opportunity set, and cash conversion cycle are the aspects taken into account in this study. The findings of a regression study using SPSS 26 indicate that, among the 43 companies chosen through purposive selection, growth potential has no bearing on cash holding, but that the cash conversion cycle and investment opportunity set do. This demonstrates that businesses with higher levels of cash holding typically have longer cash conversion cycles and significant investment prospects. This study sheds light on the critical function that cash holding plays in preserving a company's liquidity as well as the significance of financial management in the face of industrial and economic uncertainty..